Al-Kashshaf : Al-Zamakhshari's Mu'tazilite exegesis of the Qur'an - Ullah, Kifayat (De Gruyter, 2017)
"The book analyzes extensively al-Zamakhsharī's tafsīr al Kashshāf within the framework of the Mu'tazilites' five principles: (usūl al-khamsa) of their theology. Andrew Lane in his book entitled "A Traditional Mu'tazilite Qur'ān Commentary: The Kashshāf of Jār Allāh al-Zamakhsharī" states that al-Kashshāf is not a Mu'tazilite tafsīr of the Qur'ān. This book has been written to prove that al-Zamakhsharī's tafsīr is completely in accord with the Mu'tazilites' theology which is embodied in their five principles. The book is divided into two parts. Part I comprises of al Zamakhsharī's biography, al-Kashshāf, and his methodology of tafsīr. Part II covers comprehensive analysis of the five principles: unity of God; justice; the promise and the threat of divine reward and punishment; the intermediate position between belief and unbelief; and enjoining what is right and forbidding what is wrong. The book concludes that al-Zamakhsharī's al-Kashshāf is a Mu'tazilite tafsīr completely adhering to the Mu'tazilites' theology."--